Avaliação de respostas metabólicas do tambaqui exposto ao eugenol em banhos anestésicos - Inoue, Luís Antonio Kioshi Aoki; Boijink, Cheila Lima; Ribeiro, Patrizia Teixeira; Silva, Ana Maria Dias da; Affonso, Elizabeth Gusmão (Acta Amazonica, 2011)
Tambaqui is the main farmed fish in the Western Amazon. However, in handling this fish has to be anesthetized for safety purposes, usually when evaluating growth and health conditions. Eugenol, the main component of clove oil, has been reported as an alternative fish anesthetic, because it is an inexpensive natural product. However, continued studies are necessary about the metabolic responses of tropical fish to anesthetics. The present work evaluated metabolic responses of tambaqui to eugenol in simulated anesthetic baths, measuring blood and plasma parameters. Typical metabolic stress responses to handling were detected, but they were not totally reduced by eugenol. On the other hand, the anesthetic dissolved in water did not provoke any extra charge of stress during short-term exposures in concentrations of about 20mg L-1 for 15 min.
Evaluation of tambaqui metabolic responses to eugenol in anesthetics baths
Keywords: Colossoma Macropomum; Physiological Response; Hematology; Colossoma Macropomum; Respostas Fisiológicas; Hematologia